PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI STUDI PADA RUMAH MAKAN AYAM GORENG NELONGSO JLN.SURABAYA NO.56 KOTA MALANG - Iqbal Ramadhan; Hadi Sunaryo; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThe objectives of this study are: 1) To find out descriptions of Transformational Leadership, Organizational Culture, and Performance. 2) To Know the Effect of Transformational Leadership, Organizational Culture on Performance. 3) To Know the Effect of Transformational Leadership on Performance. 4) To Know the influence of Organizational Culture on Performance. 5) Knowing the Dominant Variables between Leadership and Organizational Culture on Performance. The population in this study were employees of Ayam Goreng Nelongso Jln. Surabaya No.56. The method used is the Statistical method using the help of the SPSS analysis tool. The results of this study prove that Transformational leadership and organizational culture influence the performance of the results of hypothesis testing carried out and the dominant organizational culture on performance. Keywords: Transformational Leadership, Organizational Culture, Employee Performance